Space safety and human performance - Sgobba, Tommaso; Kanki, Barbara; Clervoy, Jean-François; Sandal, Gro Mjeldheim (Oxford Butterworth-Heinemann, 2018)
Space Safety and Human Performance provides a comprehensive reference for engineers and technical managers within aerospace and high technology companies, space agencies, operators, and consulting firms. The book draws upon the expertise of the world’s leading experts in the field and focuses primarily on humans in spaceflight, but also covers operators of control centers on the ground and behavior aspects of complex organizations, thus addressing the entire spectrum of space actors. During spaceflight, human performance can be deeply affected by physical, psychological and psychosocial stressors. Strict selection, intensive training and adequate operational rules are used to fight performance degradation and prepare individuals and teams to effectively manage systems failures and challenging emergencies. The book is endorsed by the International Association for the Advancement of Space Safety (IAASS).--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Astronautics -- Human factors; Astronautics -- Safety measures; Electronic books